PENGARUH KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP LOYALITAS PEGAWAI NON MEDIS PADA RUMAH SAKIT UMUM DAERAH SANJIWANI DI KABUPATEN GIANYAR - Fitriandari, Mahayanti; Nindia Putri, Cokorda Istri Agung Vera; Ananditha, Ida Bagus Ruby (Akses: Jurnal Penelitian dan Pengabdian Kepada Masyarakat Universitas Ngurah Rai, 2024)
The study's objectives were to ascertain if job satisfaction and work motivation had a concurrent, partial, and substantial impact on the loyalty of non-medical staff at the Sanjihani General Hospital in Gianyar Regency. The proportionate random sampling technique was used to determine the sample size, which could be as many as 68 individuals. Stratified random sampling was used to carry out the sampling, meaning that the number of non-medical staff in each field under study affected how many samples were taken. The traditional assumption test, multiple linear regression coefficient analysis, determination analysis, F test statistical analysis, and t test statistical analysis were all used to analyse the data. The findings demonstrated a favourable and substantial influence on job satisfaction and work motivation on the loyalty of non-medical staff at the Sanjiwani Regional General Hospital in Gianyar Regency, either concurrently or partly.